THE RUSSIAN-UKRAINIAN WAR: CAUSES, ESSENTIAL CHARACTERISTICS, AND CONSEQUENCES FOR UKRAINE AND THE GLOBALISED WORLD - Mykola Palinchak; Yurii Ostapets; Constantin–Vasile ȚOCA (Baltic Journal of Economic Studies)
The purpose of the study is to identify the causes, essential features and consequences of the Russian-Ukrainian war for Ukraine and the globalised world. The research methodology is based on the use of general scientific methods of cognition (induction, deduction, analysis and synthesis), as well as special scientific research methods: conflict theory, neo-institutionalism, hybrid warfare theory, etc. The scientific novelty of the study lies in the fact that the authors have carried out a comprehensive analysis of the preconditions, causes and consequences of the Russian-Ukrainian war for Ukraine and the globalised world in the context of the growing confrontation between democracies and autocratic regimes. Conclusions. Firstly, the Russian-Ukrainian war has become one of the wars that have a significant impact on the globalised world: it has changed the balance of power in the international arena, demonstrated the ineffectiveness of modern security mechanisms, and is characterised by large-scale military losses and migration processes. Secondly, the main geopolitical preconditions for the war are the following: Russia's neo-imperial policy and history of relations with Ukraine, Ukraine's strategic location and European integration aspirations, and Russia's domestic policy of maintaining an authoritarian regime. In addition to the geopolitical ones, the existential preconditions of the war are also important, as Russian leaders see Ukraine's future in its accession to Russia: an ethnic, economic, geopolitical and spiritual renaissance. Thirdly, the ideological doctrine that justifies Russia's foreign expansion is the doctrine of the "Russian world". Fourthly, the Russian-Ukrainian war has large-scale consequences for both Ukraine (political, military, economic, geopolitical, social) and the globalised world (it has shown the need to reformat the international security system, led to the militarisation of the economies of the world's leading states, and intensified the global confrontation between democracies and authoritarian regimes).